A thin multifunctional coating on a separator improves the cyclability and safety of lithium sulfur batteries. Issue 9 (4th August 2017) - Xu, Guiyin; Yan, Qing-bo; Wang, Shitong; Kushima, Akihiro; Bai, Peng; Liu, Kai; Zhang, Xiaogang; Tang, Zilong; Li, Ju
Abstract : The separator has an electrocatalytic effect for polysulfide transformation, and can confine the polysulfides within the cathode and block the dendritic lithium in the anode. Abstract : Lithium–sulfur batteries are one of the most promising next-generation batteries due to their high theoretical specific capacity, but are impeded by the low utilization of insulating sulfur, unstable morphology of the lithium metal anode, and transport of soluble polysulfides. Here, by coating a layer of nano titanium dioxide and carbon black onto a commercial polypropylene separator, we demonstrate a new composite separator that can confine the polysulfides on the cathode side, forming a catholyte chamber, and at the same time block the dendritic lithium on the anode side. Lithium–sulfur batteries using this separator show a high initial capacity of 1206 mA h g −1 and a low capacity decay rate of 0.1% per cycle at 0.5C. Analyses reveal the electrocatalytic effect and the excellent dendrite-blocking capability of the ∼7 µm thick coating.